SARS-CoV-2 Infection Induces Psoriatic Arthritis Flares and Enthesis Resident Plasmacytoid Dendritic Cell Type-1 Interferon Inhibition by JAK Antagonism Offer Novel Spondyloarthritis Pathogenesis Insights - Zhou, Qiao; Vadakekolathu, Jayakumar; Watad, Abdulla; Sharif, Kassem; Russell, Tobias; Rowe, Hannah; Khan, Almas; Millner, Peter A.; Loughenbury, Peter; Rao, Abhay; Dunsmuir, Robert; Timothy, Jake; et al. (Frontiers in Immunology, 2021)
Abstract Objective. Viral infectious triggers are linked to spondyloarthritis (SpA) including psoriatic arthritis (PsA) development. Plasmacytoid dendritic cells (pDC) have a key role in mediating anti-viral responses, but their functional presence has never been investigated in the enthesis, (the primary site of inflammation in SpA). We also investigated if COVID-19 infection, triggered PsA flares. Methods. Normal entheseal pDCs were characterized and stimulated with imiquimod (TLR7) and CpG oligodeoxynucleotides (ODN) (TLR9) to evaluate TNF and IFNα production. NanoString gene expression assay of total pDCs RNA was performed pre- and post- ODN stimulation. Pharmacological inhibition of induced IFNα protein was performed with Tofacitinib, methotrexate and PDE4 inhibition. The impact of SARS-CoV2 viral infection on PsA flares was evaluated. Results. pDCs were more numerous in the enthesis than in blood, and showed inducible IFNα and TNF following ODN or imiquimod stimulation. Moreover, they were the only cell capable producing IFNα at the enthesis. NanoString data identified 11 significantly upregulated differentially expressed genes (DEGs) including TNF in stimulated pDCs. Canonical pathway analysis revealed activation of dendritic cell maturation, NF-κB signalling, toll-like receptor signalling and JAK/STAT signalling pathways following ODN stimulation. Both Tofacitinib and PDE4i strongly attenuated ODN induced IFNα. DAPSA scores elevations occurred in 18 PsA cases with SARS-CoV2 infection (9.7 ± 4 pre-infection and 35.3 ± 7.5 during infection). Conclusion. pDCs are present in the normal human enthesis, and this may provide a potential link between viral triggers and the development of SpA, however this warrants further experimental study on diseased tissue.